2011
DOI: 10.1371/journal.pone.0025678
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Osteopontin Is Highly Polymerized in Human Airways and Fragmented in Asthmatic Airway Secretions

Abstract: BackgroundOsteopontin (OPN) is a member of the small integrin-binding ligand N-linked glycoprotein (SIBLING) family and a cytokine with diverse biologic roles. OPN undergoes extensive post-translational modifications, including polymerization and proteolytic fragmentation, which alters its biologic activity. Recent studies suggest that OPN may contribute to the pathogenesis of asthma.MethodologyTo determine whether secreted OPN (sOPN) is polymerized in human airways and whether it is qualitatively different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
(79 reference statements)
0
11
0
2
Order By: Relevance
“…Possible explanations for the observation of multiple isoforms include: (1) post-translational modifications such as phosphorylation, glycosylation and addition of glycosaminoglycans, (2) protein cleavage into peptide fragments4647, (3) expression of alternative splice variants, (4) the use of alternative translational start sites76 and (5) cross-linking by transglutaminase7778. We therefore performed a systematic analysis of these factors for the wider SPARC family of proteins, combining both bioinformatics and experimental approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Possible explanations for the observation of multiple isoforms include: (1) post-translational modifications such as phosphorylation, glycosylation and addition of glycosaminoglycans, (2) protein cleavage into peptide fragments4647, (3) expression of alternative splice variants, (4) the use of alternative translational start sites76 and (5) cross-linking by transglutaminase7778. We therefore performed a systematic analysis of these factors for the wider SPARC family of proteins, combining both bioinformatics and experimental approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitantly, polymerized forms of OPN (similar to the structure of OPN, which was polymerized by TGM2) were detected in mice with asthma and enhanced after exposure to viruses. In addition, the polymerized form of OPN was found in asthmatic airways, while fragmented forms were found in the airway secretion of patients with asthma 23 . Although we could not find a direct effect of OPN on TGM2 formation, the current findings led us to speculate that viral infection and aging may stimulate TGM2 polymerization, which further enhances collagen binding.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil-derived OPN was shown to contribute to fibrosis through the IL-33/ amphiregulin (Areg)/epidermal growth factor receptor (EGFR) axis in the context of Th2 inflammation 21 . Recent functional studies demonstrated that OPN presents as the polymerized form due to the effect of tissue transglutaminase 2 (TGM2) in the human airways, which increases its collagen-binding activity 22,23 . Accumulating evidence suggests that OPN is a key cytokine in the modulation of inflammation and fibrotic events in asthmatic airways.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed to investigate the size distribution of OPN in CF sputum and in induced sputum from healthy controls. Both polymerization and degradation of OPN has been observed in asthma and polymerized OPN is chemotactic against neutrophils through binding α 9 β 1 integrins [18,19]. The full-length protein migrated around 65 kD after SDS-PAGE ( Fig.…”
Section: Polymers and Fragments Of Opn In Cf Sputummentioning
confidence: 90%